DIGITAL LITERACY IMPACT ON PERCEIVED USEFULNESS, PERCEIVED EASE OF USE AND ONLINE PURCHASE INTENTION IN PAKISTAN - Shumaila Israr; Sidra Khan; Aisha Riaz (Policy Research Journal, 2024)
This study investigates the impact of digital literacy on perceived usefulness, perceived ease of use, and online purchase intention in Pakistan. With the rapid expansion of e- commerce in the country, digital literacy has become an essential factor influencing consumer behavior in the online shopping environment. The research uses a quantitative approach, collecting data from 500 respondents across urban and semi-urban areas of Pakistan. A structured questionnaire was designed to measure the variables: digital literacy, perceived usefulness, perceived ease of use, and online purchase intention. The data analysis, conducted using Structural Equation Modeling (SEM), reveals that digital literacy has a significant positive effect on both perceived usefulness and perceived ease of use of e-commerce platforms. In turn, these perceptions significantly influence online purchase intention. The findings suggest that enhancing digital literacy among consumers can lead to increased engagement with e-commerce platforms, making them more accessible and user-friendly. This research contributes to the understanding of how digital literacy shapes online shopping behavior in Pakistan, offering valuable insights for e-commerce businesses and policymakers aiming to promote digital inclusion and optimize user experiences.